Investigating suicidality across the autistic-catatonic continuum in a clinical sample of subjects with major depressive disorder and borderline personality disorder - Dell’Osso, Liliana; Nardi, Benedetta; Bonelli, Chiara; Gravina, Davide; Benedetti, Francesca; Amatori, Giulia; Battaglini, Simone; Massimetti, Gabriele; Luciano, Mario; Berardelli, Isabella; Brondino, Natascia; De Gregorio, Marianna; et al. (Frontiers in Psychiatry, 2023)
Background: Recent literature has highlighted that catatonia may be more prevalent among psychiatric patients than previously thought, beginning from autism spectrum disorders (ASD), for which it has been suggested to represent a severe late consequence, but also among individuals with mood disorders and Borderline personality disorder (BPD). Interestingly, one critical point shared by these conditions is the increased risk of suicidality. The aim of this study was to evaluate how the presence and the prevalence of catatonic symptoms may shape and correlate with suicidal risk in a sample of individuals with Major depressive disorder (MDD) or BPD. Methods: We recruited two clinical samples of subjects (BPD and MDD) and a control group without a diagnosis according to DSM-5 (CTL). Subjects were assessed with the Catatonia Spectrum (CS) and the MOODS-SR for evaluating suicidality. Results: In the total sample, suicidality score was significantly and positively correlated with all CS domains and CS total score. Correlation and regression analyses highlighted specific patterns of association among Catatonia Spectrum domains and suicidality in the MDD and BPD group and in the total sample. Conclusions: In both disorders, higher catatonic traits are linked to higher suicidal tendencies, confirming the high risk of suicide for this population. However, different patterns of association between catatonic symptoms and suicidality were highlighted in the two disorders.